Directed synthesis and search of pharmaceutical substances with hypoglycemic activity in the series of 4-aryl-2-hydroxy-4-oxo-2-butenoic acids - N. A. Pulina; A. I. Krasnova; F. V. Sobin; T. A. Yushkova; V. V. Yushkov (Бюллетень сибирской медицины)
The paper deals with directed synthesis and study of hypoglycemic activity of N-heterylamides of 4-aryl-2-hydroxy-4-oxo-2- butenoic and 4-aryl-3-bromo-2, 4-dioxobutanoic acids. Hypoglycemic activity of 28 compounds was under research. Some regularities of the influence of the heterocyclic moiety structure and the bromine atom on the activity of the compounds were obtained. Two low-toxic and highly active substances comparable in potency with the reference drug were identified.